Surveyor Analysis of Centralized and Distributed Association Rule Mining Algorithm (International Journal of Food and Nutritional Sciences, 2021)
Among various data mining methods, Association Rule Mining (ARM) is particularly popular. However, ARM often generates a vast number of rules, making it challenging for analysts to identify the most relevant ones. Traditional approaches, such as Apriori, rely on generating and testing candidate element, which can be computationally expensive, especially for large datasets with long patterns. Power full Element set compute algorithms, an elongation of Apriori, enhance the efficiency of elements et mining by dynamically updating element set counts during the mining process. Here’s a breakdown of how DIC algorithms work and how they improve upon the original Apriori algorithm: offer a more efficient alternative by reducing the number of scans required. These algorithms dynamically add and delete element sets as transactions are processed, focusing only on element DIC algorithm offers an efficient approach to frequent element set mining by focusing on managing element dynamically and leveraging the properties of frequent subsets to streamline the process.